Suffering Our Way to Salvation: Ivone Gebara, Elisabeth Schüssler Fiorenza, and the Adequacy of the Cross as a Symbol for Women - Chapman, Amy (Lumen et Vita, 2011)
This article explores the theologies of the cross and salvation put forth by Brazilian liberation theologian Ivone Gebara and American theologian Elizabeth Schüssler Fiorenza. Both scholars depart from a traditional Anselmian theology of the cross and salvation, holding that for some women Anselm’s understanding is insufficient. Both theologians claim that within Anselm’s theology of the cross and salvation is the understanding that suffering is necessary for salvation. Wishing to dispute that, Gebara examines the lived experiences of women while Schüssler Fiorenza focuses on references from scripture. Both women arrive at the conclusion that the cross proves to be an inadequate symbol for salvation for some women, and Schüssler Fiorenza provides the empty tomb as an alternative symbol.